Assessment of the potential public health impact of Herpes Zoster vaccination in Germany. Issue 10 (3rd October 2017) - Curran, Desmond; Van Oorschot, Desirée; Varghese, Lijoy; Oostvogels, Lidia; Mrkvan, Tomas; Colindres, Romulo; von Krempelhuber, Alfred; Anastassopoulou, Anastassia
ABSTRACT: The aim of this study was to compare the public health impact of introducing 2 Herpes Zoster (HZ) vaccines, Zoster Vaccine Live (ZVL) versus a non-live adjuvanted subunit candidate vaccine (HZ/su), in the German population aged 50+ years split into 3 age cohorts, i.e. 50–59, 60–69 and 70+ years, respectively. A multi-cohort static Markov model was developed following age cohorts over their lifetime. Demographic data were obtained from the German federal statistical office. HZ incidence and the proportion of HZ individuals developing post-herpetic neuralgia (PHN) were derived from German specific sources. Age-specific vaccine efficacy and waning rates were based on published clinical trial data. Vaccine coverage for both vaccines was assumed to be 40%, with compliance of the second dose of the HZ/su vaccine of 70%. Sensitivity analyses were performed to assess the robustness of the results. It was estimated that, over the remaining lifetime since vaccination, the HZ/su vaccine would reduce the number of HZ cases by 725, 233, 533, 162 and 486, 794 in the 3 age cohorts, respectively, compared with 198, 477, 196, 000 and 104, 640, using ZVL. The number needed to vaccinate (NNV) to prevent one HZ case ranged from 8 to 11 using the HZ/su vaccine compared with 20 to 50 using ZVL. Corresponding NNV to prevent one PHN case ranged from 39 to 53 using the HZ/su vaccine compared with 94 to 198 using ZVL. Due to the higher, sustained vaccine efficacy, the candidate HZ/su vaccine demonstrated superior public health impact compared with ZVL.